The common good in the Political Constitution of Peru of 1993 - Páucar Lino, Antonio (2019)
The common good as a spiritual, moral and corporal strength of the human being is introduced in the definition and exercise of constitutional property, which fulfills a role of guarantee of investment and legal security in the country. Therefore, we will explain in this article the important role it plays in society.